EFEKTIVITAS MODEL DISCOVERY LEARNING BERBANTUAN MEDIA CANVA DALAM MENINGKATKAN KETERAMPILAN MENULIS IKLAN SISWA KELAS VIII - Sindi Sopiah; Teti Sobari; Via Nugraha (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
This research is motivated by the low interest in writing students in learning explanatory texts in grade XI high school students. The purpose of this study was to determine the application of the Problem Based Learning model assisted by YouTube media in learning explanatory texts for grade XI high school students. The subjects of the study involved 33 students of grade XI MIPA 8 SMAN 1 Tempuran. The research method used was a mix method with an exploratory sequential design that combines two research methods, namely qualitative and quantitative methods. Qualitative data were obtained through observation sheets and questionnaires, quantitative data were obtained through tests in the form of pretests and posttests. Based on the results of observations and questionnaires carried out in the learning process using the Problem Based Learning model assisted by YouTube media, it was categorized as very good. The results of the pretest and posttest on the N-gain test obtained an average value of 0.6116. The average value is 30 ≤ N Gain ≤ 70. The average significance level is stated in the "moderate" category. The average N-Gain value in the form of a percentage is 61.1637. The value is in the range of 56-75 with an interpretation of "quite effective". It can be concluded that the use of the Problem Based Learning model assisted by YouTube media is interpreted as being quite effective.